Your best life now 7 steps to living at your full potential - Osteen, Joel (New York, N.Y. : Time Warner AudioBooks, 2004)
Counsels listeners to draw on innate strengths in order to overcome obstacles, promote personal health, and live abundantly, in a guide that advises listeners to act in accordance with God's intentions rather than personal feelings
Title from container
Keywords: Self-actualization (Psychology) -- Religious aspects -- Christianity; Success -- Religious aspects -- Christianity